Pertanggungjawaban Hukum Pidana terhadap Malpraktik Medis pada Rumah Sakit - Renita Meidiana Putri; Akhmad Munawar; Sudiyono (CV Rewang Rencang, 2023)
Malpractice is an error or negligence committed by professional staff, such as doctors, lawyers, accountants, dentists or veterinarians, which do not comply with professional standards. In reality, malpractice still often occurs, both in hospitals and medical personnel, even though there are several legal instruments that regulate hospitals and medical practice with sanctions for violators of health laws. The aim of this research is to explore existing deficiencies in legal policies, and propose new legal policies in order to optimally prevent and overcome hospital malpractice. The research method used is a normative research method by examining aspects of criminal law in health law regarding malpractice, as well as theories and expert opinions for better legal policy proposals. From the qualitative analysis of data on primary and secondary legal materials, the following results were obtained: first, there are weaknesses in the health law policy so that it cannot prevent and deal with malpractice optimally, namely the lack of completeness and lack of clarity regarding the formulation of malpractice and its strict sanctions, and a turn towards acts of resistance. the law and limitations of the hospital's responsibility for malpractice committed by doctors or medical personnel. Second, a new legal policy that can be proposed is by formulating clearly and in detail the limits of hospital malpractice in health law, accompanied by strict sanctions or accountability both criminally, civilly and administratively, hospitals.